Gap Analysis of ISO 9001:2015 in HRD Department of PT. Citra Abadi Sejahtera (Journal of Wetlands Environmental Management, 2024)
ISO 9001:2015 is a Quality Management System that to assist the operational business processes of each organization to achieve the vision and mission that has been set by the organization. Management's responsibility is to provide resources, including material, machines, humans, methods and money. Basically, the strength that exists in a company lies in the human resources (HR) in the company. If HR is treated properly and in accordance with its dignity, the company will achieve results in accordance with the goals desired by the company. The benefits of implementing ISO 9001:2015 certification for companies cause a positive assessment of the company's reputation. The ISO 9001:2015 certification implementation system also emphasizes customer-focused business processes, understanding customer needs and increasing customer satisfaction. In ISO 9001, Internal Audits must be carried out on companies or organizations to determine whether the implementation of the quality management system is running, and the internal audit can be a reference and preparation for later if there is an external audit from the certification body. Through the Gap Analysis checklist, it will facilitate the analysis of ISO requirement elements in the form of a checklist. Gap Analysis is effective because the checklist created is structured and in accordance with the topic. The checklist will cover all existing requirements and is made hierarchically in its assessment, this will include general questions and provide an overview of the topic or category to be assessed. The results showed a difference in the gap of 8.1% with a score of 91.9%. This indicates that Citra Abadi Sejahtera corporation is ready to implement ISO 9001:2015 and conduct certification. However, Citra Abadi Sejahtera corporation needs to make improvements according to the checklist that refers to the requirements of ISO 9001:2015 to cover the gap, especially by implementing the PDCA (Plan-Do-Check-Act) cycle.